Phenology and fruit biometrics in different positions of reproductive branches of Campomanesia adamantium (Cambess.) O. Berg - Assis, Marília dos Santos (2020)
Abstract Phenology is very important to the understanding of plant cycles, the repetition of biological events, and the causes of these cycles in relation to abiotic selective factors and biotic factors. The aims of this to evaluate the time of occurrence and intensity of the vegetative and reproductive phenological phases, their correlations with external factors, and the influence of photosynthetically active radiation in the fruit Campomanesia adamantium (Cambess.) O. Berg. The study was conducted on a farm in the municipality of Rio Verde, Bazil. The phenological characterisation was performed using ten adult plants. Phenological observations of vegetative and reproductive phenophases were made monthly and weekly, respectively. The total number and the transverse and longitudinal diameters of the fruit of two branches per plant, with higher and lower incidence of radiation, were also evaluated. The young and adult leaves in Campomanesia adamantium were active for almost the entire study period, except the young leaves were inactive in the months of May and August. The presence of sprouts was also very high during the study period. There was a phenophase cycle of rapid and intense play between October and January for C. adamantium. The incidence of radiation interfered with the size and production of the fruit. Fruits that developed in the shadow of branches were fewer and their biometric values ​​lower than those who developed in sunlight.